A bit thick: Hidden risks in thickening products' labelling for dysphagia treatment. (February 2022) - Bolivar-Prados, M.; Tomsen, N.; Arenas, C.; Ibáñez, L.; Clave, P.
Abstract: Thickening products (TPs) are a valid therapeutic strategy in patients with oropharyngeal dysphagia, their effect is mainly related to the bolus viscosity achieved. The aim of the study was to compare the information on the labels of 10 TPs of different thickening agents (hydrocolloids): modified starch-based, gum-based and mixtures. Viscosity was measured in SI units (mPa·s), using a rotational viscometer at 50 s −1 and 300 s −1, and the effect of oral amylase (α-SA) and shear thinning on the viscosity levels recommended by each manufacturer were assessed. Results were classified according to 3 textural classifications: National Dysphagia Diet (NDD), International Dysphagia Diet System (IDDSI) and Japanese Dysphagia Diet (JDD2013). Results are also presented in SI units (mPa·s) following a new proposed scientific labelling system developed in our laboratory at Hospital de Mataró and endorsed by eleven medical and scientific societies. The effect of α-SA was assessed after 30 s oral incubation of the thickened bolus. All TPs fulfil Food for Special Medical Purposes labelling regulations, use 3 thickness levels, and 70% use the NDD descriptors. Viscosities at 50 s −1 ranged between 75 and 350 mPa s for level 1, 256–1280 for level 2 and 377–6205 for level 3. α-SA caused 98–99% decrease in viscosity for modified starch-based TPs (MS) and 16% or even an increment for gum-based TPs. Shear thinning decreased viscosity from 40 to 60% for MS-based TPs and 70–75% for gum-based TPs. This study showed that TPs are commercialised using the same descriptors for very different viscosities when measured in mPa·s. Shear rate and α-SA strongly affect viscosity but this is not described on the labels. We claim labels should include viscosity in SI Units (mPa·s at 50 s −1 ) and the effect of α-SA and shear thinning as main factors affecting the therapeutic effect and mode of action of thickening agents. Graphical abstract: Image 1